1943
DOI: 10.1093/oxfordjournals.bmb.a070193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protein Intake on the Absorption of Calcium and Magnesium

Abstract: Lehmann & Pollak [1942a] observed that the phosphates and carbonates of Ca and Mg were much more soluble in solutions of oa-amino-acids than they were in pure water, and it has since been shown that the solubility of commercial 'phytin ' can be increased in the same way. In consequence of their observations, Lehmann & Pollak suggested that amino-acids might facilitate the absorption of Ca. To prove or disprove this hypothesis, it was decided to study in human subjects the effect of varying protein consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1948
1948
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…Such assessments require an evaluation under a carefully controlled dietary regimen, since these measurements are markedly sensitive to dietary perturbations. It is well known that the renal excretion of calcium is influenced by variation in the dietary intakes of calcium (3), phosphorus (15), sodium (16), and proteins (17). Further, parathyroid function may be normally dependent on the oral intake of calcium (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such assessments require an evaluation under a carefully controlled dietary regimen, since these measurements are markedly sensitive to dietary perturbations. It is well known that the renal excretion of calcium is influenced by variation in the dietary intakes of calcium (3), phosphorus (15), sodium (16), and proteins (17). Further, parathyroid function may be normally dependent on the oral intake of calcium (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of HP diet on calcium intestinal absorption is unclear (Table 2). McCance et al (1942) first observed that subjects consuming a LP diet (o70 g/day) had a 20% decrease of intestinal calcium absorption compared with those consuming a HP diet (4145 g/day). These first findings were confirmed by …”
Section: Modulations Of Intestinal Dietary Calcium Absorptionmentioning
confidence: 99%
“…Results of earlier studies indicated that an increase in protein intake caused increases in urinary calcium and apparent absorption of calcium (1)(2)(3)(4), and the prevailing opinion has been that a high protein intake has a beneficial effect on calcium retention by causing an increase in calcium absorption.…”
Section: Discussionmentioning
confidence: 99%